2014
DOI: 10.1063/1.4901733
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of optical and electrical noise equivalent power of hybrid NbTiN-Al microwave kinetic inductance detectors

Abstract: We have measured and compared the response of hybrid NbTiN-Al Microwave Kinetic Inductance Detectors (MKIDs) to changes in bath temperature and illumination by sub-mm radiation. We show that these two stimulants have an equivalent effect on the resonance feature of hybrid MKIDs. We determine an electrical NEP from the measured temperature responsivity, quasiparticle recombination time, superconducting transition temperature and noise spectrum, all of which can be measured in a dark environment. For the two hyb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Importantly Janssen et al (2014) have shown that the dark NEP is a good approximation for the NEP measured using a calibration source for the hybrid NbTiNAl MKID design. We give, in Fig.…”
Section: Dark Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly Janssen et al (2014) have shown that the dark NEP is a good approximation for the NEP measured using a calibration source for the hybrid NbTiNAl MKID design. We give, in Fig.…”
Section: Dark Sensitivitymentioning
confidence: 99%
“…keeping the radiator in dark conditions, i.e. T BB = 2.7 K. Under these conditions the amount of quasiparticles in the aluminium N qp can be calculate from the chip temperature, the volume of the aluminium section of the resonator and the energy gap (Janssen et al 2014). Rewriting N qp in terms of FIR power allows the dark NEP to be calculated using Eq.…”
Section: Dark Sensitivitymentioning
confidence: 99%
“…MKIDs are photon noise limited for various frequencies [10][11][12][13][14][15] . The level of experimental detail that has now been achieved 13,16,17 calls for a more detailed understanding of the absorption of radiation. An important gap in this understanding is a measurement of η pb .…”
mentioning
confidence: 99%
“…To estimate performance of the prototype device from a detector perspective, we measure the electrical noise equivalent power (NEP). It has recently been shown that an estimate of electrical NEP provides an accurate indication of the optical performance for devices where the contribution to the responsivity is constant across the absorbing volume [11]. For a leKID, this is automatically satisfied as the current density across the inductor is constant.…”
Section: Preliminary Resultsmentioning
confidence: 99%